Frequency and Implications of Complications in the ICU After Status Epilepticus: No Calm After the Storm*. Issue 12 (December 2020) - Baumann, Sira M.; Semmlack, Saskia; De Marchis, Gian Marco; Hunziker, Sabina; Rüegg, Stephan; Marsch, Stephan; Sutter, Raoul
Abstract : Objectives: To investigate the frequency, types, and implications of complications during intensive care in patients after status epilepticus has been successfully terminated. Design: Retrospective study. Setting: ICUs at a Swiss tertiary academic medical care center. Patients: Data were collected from the digital patient records of all adult patients with status epilepticus from 2012 to 2018. Interventions: None. Methods: Primary outcomes were defined as frequency of complications following status epilepticus termination and return to premorbid functional baseline. Univariable analyses regarding the relative risks of complications occurring after status epilepticus termination for no return to premorbid neurologic function were estimated by Poisson regression with robust error variance. Results: Of 311 patients with status epilepticus, 224 patients (72%) were treated on the ICU for more than 24 hours following status epilepticus termination. Ninety-six percent of patients remained in a prolonged state of altered consciousness for a median of 2 days (interquartile range, 1–3 d) and 80% had complications during their ICU treatment. Fifty-five percent had new-onset delirium with a median duration of 2 days (interquartile range, 1–3 d). Forty-two percent had mechanical ventilation for a median of 4 days (interquartile range, 2–11 d) and 21% had nosocomial infections diagnosed after status epilepticus. Multivariable analyses revealed that mechanical ventilation for more than 24 hours after status epilepticus, and arterial hypotension requiring vasopressors were independently associated with increased risk of no return to premorbid function (RRfor each additional day = 1.01; 95% CI, 1.02–1.03 and RRfor each additional day = 1.03; 95% CI, 1.01–1.05) and death (RRfor each additional day = 1.11; 95% CI, 1.04–1.19 and RRfor each additional day = 1.15; 95% CI, 1.03–1.28). Delirium was independently associated with a decreased relative risk of death (RRfor each additional day = 0.55; 95% CI, 0.37–0.80), but prolonged ICU- and hospital stays. Conclusions: Complications after status epilepticus termination are frequent and associated with no return to premorbid function, death, and prolonged ICU- and hospital stays. These results call for heightened awareness and further studies mainly regarding prediction and preventive strategies in this context. Abstract : Supplemental Digital Content is available in the text.